2012
DOI: 10.1111/j.1523-5378.2012.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Gemifloxacin Can Partially Overcome Quinolone Resistance of H. pylori with gyrA Mutation in Taiwan

Abstract: Gemifloxacin is superior to levofloxacin in antimicrobial activity against clinical H. pylori isolates, and even overcome some levofloxacin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
(40 reference statements)
4
19
0
Order By: Relevance
“…Besides, a cross resistance pattern was observed across different generations of fluoroquinolone (moxifloxacin > levofloxacin > ciprofloxacin > gemifloxacin) with high chance of developing fluoroquinolone resistance as a result of other treatments prior to H. pylori eradication. Similar to an early report on the Taiwanese population [15], the degree of resistance to gemifloxacin was low in the Malaysian population suggested that it may have better drug efficacy than levofloxacin in H. pylori eradication in our population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Besides, a cross resistance pattern was observed across different generations of fluoroquinolone (moxifloxacin > levofloxacin > ciprofloxacin > gemifloxacin) with high chance of developing fluoroquinolone resistance as a result of other treatments prior to H. pylori eradication. Similar to an early report on the Taiwanese population [15], the degree of resistance to gemifloxacin was low in the Malaysian population suggested that it may have better drug efficacy than levofloxacin in H. pylori eradication in our population.…”
Section: Discussionsupporting
confidence: 90%
“…As a counter measure, fluoroquinolone-containing triple and bismuth-containing quadruple therapies have also been proposed as second line therapies after the failure of the clarithromycin-containing treatment [12], [13]. In spite of that, a number of studies have shown a low but rapid rise of fluoroquinolone-resistance in countries where fluoroquinolone has been widely prescribed [14], [15], [16], [17], [18], [19]. To date, the mechanisms underlying the resistance to metronidazole, clarithromycin and flouroquinolones remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase in fluoroquinolone resistance has become a significant limitation for providing effective H. pylori eradication. Newly developed fluoroquinolones, such as gemifloxacin, clinafloxacin, and sitafloxacin, have been studied and demonstrated favorable outcomes for treatment of H. pylori (27). In particular, sitafloxacin has been reported to show outstanding antimicrobial efficacy even for microorganisms with gyrA mutations (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…One may need to choose a more potent quinolone in order to prevent the development of quinolone resistance during anti- H. pylori therapy. One recent study from Taiwan showed that gemifloxacin was superior to levofloxacin in antimicrobial activity against H. pylori isolates and even overcame some levofloxacin resistance [52]. Gemifloxacin is a powerful potent quinolone against H. pylori .…”
Section: The Impact Of Quinolone Exposure On Tuberculosismentioning
confidence: 99%